Aplicación del aprendizaje cooperativo en el proceso de enseñanza - aprendizaje de los niños y niñas del primer año de educación básica en la Escuela Mariscal Sucre de la ciudad de Machala durante el año lectivo 2012-2013. - Herrera Sagbay, Mónica Cecilia (2013)
This research is based on the implementation of cooperative learning in the teaching - learning, without cooperation can not learn in class the children who are more likely to learn are those who are better able to work together. Cooperative learning has been recommended as the most effective in the process of teaching and learning technique.